Enforcement of purpose trusts in Bermuda: a recent decision of the Court of Appeal. Issue 3 (2nd October 2015) - Robinson, Keith
Abstract : Legislation in many offshore jurisdictions now provides for purpose trusts, but how do these creatures of statute fit into the broader legal landscape? This article considers a recent Bermuda case concerning assertions of privilege by trustees of purpose trusts in the context of a hotly contested Beddoes proceeding. The Bermuda court at both first instance and on appeal had to grapple with who was entitled to enforce a Bermuda purpose trust and how this question impacted upon the law of privilege. As will be explained, many questions remain unanswered.